A comprehensive study on the effects of alternative sulphur precursor on the material properties of chemical bath deposited CdS thin films. Issue 11 (1st August 2020) - Azmi, N.; Chelvanathan, P.; Yusoff, Y.; Shahahmadi, S.A.; Tiong, S.K.; Sopian, K.; Amin, N.
Abstract: Chemical bath deposition (CBD) method was used to deposit CdS thin films on soda-lime glass substrates by using n-methylthiourea (NTU) as an alternative sulphur source and were compared to typical thiourea (TU) precursor. The sulphur source concentration was varied from 0.01 M to 0.1 M and the impact on the microstructural, surface morphology, optical and electrical properties of the grown films were studied. Increasing n-methylthiourea concentration in the precursor yielded thinner films that are less than 100 nm thickness, surface morphology with average surface roughness of 6.4 nm, larger granular structure, wider band gap at 2.3 eV–2.6 eV range. Raman spectroscopy revealed Raman peak at 303 cm-1. In contrast, an increase in thiourea concentration resulted in thinner amorphous films, less distinct granular structure, narrower energy band gap from 2.3 eV to 2.4 eV and a resonance Raman peak at 302 cm-1. CdS thin film deposited from n-methylthiourea precursor at higher precursor concentration of 0.1 M showed better electrical properties such as lower resistivity and higher carrier mobility compared to the thin film deposited from typical thiourea precursor.